2020
DOI: 10.1186/s43055-019-0129-1
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for ductus venosus flow in normal gestation among an Egyptian population

Abstract: Background: Doppler studies of the fetal circulation have demonstrated the importance of the ductus venosus in the continuous monitoring of fetuses, especially those of high-risk pregnancies that can lead to abnormal pregnancy outcome. We tried to put reference values for the normal ductus venosus (DV) flow in normal gestation to be used in further studies assessing the different pathologies. Results: The DV length ranged from 9.8 to 20.9 mm, and the diameter ranged from 0.6 to 2.3 mm. The DV pulsatility index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Our results showed that DV shunt rate (Q DV /Q UV ) was negatively correlated with gestational age, a finding also reported by Zytoon et al 5 and Kiserud et al 12 In addition, the DV shunt rate of fetuses with FGR is higher than that of normal fetuses, a result consistent with that of Ritter et al 17 Their study showed that when the fetus is ischemic and hypoxic, the proportion of blood flow of the UV entering the DV increases to 90%. Under pathological conditions, such as during abnormal fetal heart development, fetal growth restriction, fetal chromosomal abnormality, intrauterine hypoxia, and other changes that affect the structure and function of the heart; abnormal vascular development or blood composition can cause fetal protective hemodynamic adaptations, which directly affect the shape and blood flow spectra and waveforms of the DV, its blood flow, and the shunt rate.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results showed that DV shunt rate (Q DV /Q UV ) was negatively correlated with gestational age, a finding also reported by Zytoon et al 5 and Kiserud et al 12 In addition, the DV shunt rate of fetuses with FGR is higher than that of normal fetuses, a result consistent with that of Ritter et al 17 Their study showed that when the fetus is ischemic and hypoxic, the proportion of blood flow of the UV entering the DV increases to 90%. Under pathological conditions, such as during abnormal fetal heart development, fetal growth restriction, fetal chromosomal abnormality, intrauterine hypoxia, and other changes that affect the structure and function of the heart; abnormal vascular development or blood composition can cause fetal protective hemodynamic adaptations, which directly affect the shape and blood flow spectra and waveforms of the DV, its blood flow, and the shunt rate.…”
Section: Discussionsupporting
confidence: 91%
“…The normal reference value ranges of fetal DA and DV blood flows have been defined, 4 , 5 but few reports on DA and DV shunt rates exist. Ultrasound variables have been used to estimate fetal body mass, abdominal circumference and growth rate indicators; 6 but, its value for diagnosing and predicting fetal growth restriction (FGR) and the perinatal prognosis of high-risk fetuses is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in vivo experiments provided a foundation for fetal circulation studies, such studies are limited to animal models due to their highly invasive nature. Detailed information regarding human fetal circulation was made possible by the development of fetal ultrasound [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. FitzGerald and Drumm (1977) are credited with creating a reliable non-invasive technique to investigate fetal blood flow using a combination of echo and Doppler ultrasound [ 70 ].…”
Section: Fetal Cardiovascular Physiologymentioning
confidence: 99%
“…6 N = 133 subjects, peak velocity (Doppler) [65]; N = 2310 subjects, diameter (ultrasound measurements) [69]. 7 N = 230 subjects, peak velocity (Doppler) [66]; N = 230 subjects, diameter (ultrasound measurements) [66].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%